0237 Sleep Reactivity Prospectively Predicts Distress Reactions to the COVID-19 Pandemic 3-4 Years Later. (25th May 2022) - Reffi, Anthony; Cheng, Philip; Kalmbach, David; Sultan, Zain; Drake, Christopher
Abstract: Introduction: The 2019 coronavirus disease (COVID-19) pandemic is a protracted stressor with far-reaching effects on daily life. Although most individuals exhibit resilience in the wake of adversity, it is not clear which characteristics reliably predict resilience versus longstanding distress. It is vital to delineate predictors of pandemic-related distress to highlight modifiable risk factors that can be targeted to enhance psychological resilience. Sleep reactivity may be an important predictor of pandemic reactions because it reflects a vulnerability to experience pronounced sleep disturbances in response to stress, which serve as barriers to healthy adjustment to adversity. Therefore, this study tested sleep reactivity as a prospective predictor of pandemic-related distress. Methods: Participants were recruited from a previous randomized controlled trial (RCT) comparing self-guided digital CBT-I against a sleep education control in treating insomnia and preventing depression. Participants in the RCT were enrolled between 2016-2017 and were eligible for this follow-up study conducted between April and May 2020 (N = 208; dCBT-I: n = 102; control: n = 106). Pre-treatment sleep reactivity was measured in 2016-2017 (T1) using the Ford Insomnia Response to Stress Test (FIRST). COVID-19 distress was measured in April 2020 (T2) using the Impact of Events Scale (IES) and Quick Inventory of Depressive Symptomatology (QIDS). All analyses controlled for treatment condition and COVID-19 impact. Results: T1 FIRST predicted T2 IES (b = 0.29, + 0.14 SE, p < .05) and QIDS (b = 0.16, + 0.04 SE, p < .001), such that higher sleep reactivity pre-pandemic predicted more severe stress responses and depressive symptoms during the pandemic 3-4 years later. Exploratory analyses revealed T1 FIRST was a predictor of the IES subscales arousal and intrusions (bs = 0.02, + 0.01 SEs, ps < .05), but not avoidance. Conclusion: These findings build on evidence that sleep reactivity prospectively predicts reactions to trauma and demonstrate its predictive utility generalizes to pandemic responses. Sleep reactivity is a modifiable risk factor that may be targeted using cognitive-behavioral or mindfulness-based approaches, and thus may offer a new pathway to resilience. Support (If Any): Support for P.C. was provided from the National Heart Lung and Blood Institute (K23HL138166).